2024
DOI: 10.3390/brainsci14030296
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Functional Magnetic Resonance Imaging Time Series in Glioblastoma Characterization: A Review of the Evolution, Applications, and Potentials

Matteo De Simone,
Giorgio Iaconetta,
Giuseppina Palermo
et al.

Abstract: In this paper, we discuss how the clustering analysis technique can be applied to analyze functional magnetic resonance imaging (fMRI) time-series data in the context of glioblastoma (GBM), a highly heterogeneous brain tumor. The precise characterization of GBM is challenging and requires advanced analytical approaches. We have synthesized the existing literature to provide an overview of how clustering algorithms can help identify unique patterns within the dynamics of GBM. Our review shows that the clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…fMRI, pioneered in the 1990s by Seiji Ogawa and Kenneth Kwong, tracks brain activity via blood flow and oxygen levels, known as blood oxygenation level-dependent (BOLD) imaging [ 20 , 21 ]. Active brain areas display increased oxygen consumption and blood flow, appearing brighter on fMRI scans [ 22 ].…”
Section: Imagingmentioning
confidence: 99%
“…fMRI, pioneered in the 1990s by Seiji Ogawa and Kenneth Kwong, tracks brain activity via blood flow and oxygen levels, known as blood oxygenation level-dependent (BOLD) imaging [ 20 , 21 ]. Active brain areas display increased oxygen consumption and blood flow, appearing brighter on fMRI scans [ 22 ].…”
Section: Imagingmentioning
confidence: 99%
“…The advantages of mastering this technique include reduced morbidity, no visible scarring or external craniotomies, and minimal brain manipulation. Good preoperative selection also comes through a thorough study of the anatomy; an EANS survey on experienced skull base surgeons showed that most respondents use both MRI and CT scans preoperatively to study the anatomy [5,6].…”
Section: Introductionmentioning
confidence: 99%